Analysis of Plasma Multiplex Cytokines for Children With Febrile Seizures and Severe Acute Encephalitis. (February 2014) - Hu, Mei-Hua; Huang, Go-Shine; Wu, Chang-Teng; Lin, Jainn-Jim; Hsia, Shao-Hsuan; Wang, Huei-Shyong; Lin, Kuang-Lin
We investigated the plasma cytokine profiles of children with febrile seizures or severe acute encephalitis using multiplex cytometry to evaluate the role of cytokines in these diseases. Interleukin-6, -10, -12p70, -17A, -2, -4, -5, -9, -13, -22, and -1β, interferon-γ, and tumor necrosis factor-α were measured in the plasma from children with febrile seizures (n = 9) or severe acute encephalitis (n = 21). In multivariate analysis, interleukin-6 was significantly increased in the plasma of the febrile seizure patients compared to those with severe acute encephalitis, suggesting that interleukin-6 is activated during the acute stage of a febrile seizure. A lower plasma interleukin-6 concentration was significantly associated with severe acute encephalitis. The cytokine network may be deregulated in severe acute encephalitis via the persistence of an uncontrolled inflammatory state in the brain.